The Role of Electronic Receipt and Payment Instruments in the Development of Banking Services - Fathollah Tari; Hanieh Raeisi (Iranian Journal of Accounting, Auditing & Finance)
The development of E-banking plays an essential role in the performance of the economy. This paper examines whether and how the use of electronic devices affects banking transactions? To answer this question, this paper uses the Chakravorti model that estimated this relationship in the United States and employs the data of Iran’s banking system for ten banks — including Melli, Sepah, Saderat, Tejarat, Mellat, Refah, Saman, Parsian, Eghtesad Novin, and Pasargad — over 2009 to 2017. The results show that all three positively affect bank cards' volume of transactions among ATMs, POS terminals, and bank cards. In the meantime, the effectiveness of ATMs is more than sale terminal devices.